Environmentally controlled bacterial vesicle‐mediated export - Orench‐Rivera, Nichole; Kuehn, Meta J. (Cellular microbiology, 2016)
Over the past two decades, researchers studying both microbial and host cell communities have gained an appreciation for the ability of bacteria to produce, regulate, and functionally utilize outer membrane vesicles (OMVs) as a means to survive and interact with their cellular and acellular environments. Common ground has emerged, as it appears that vesicle production is an environmentally controlled and specific secretion process; however, it has been challenging to discover the principles that govern fundamentals of vesicle‐mediated transport. Namely, there does not appear to be a single mechanism modulating OMV export, nor universal “markers” for OMV cargo incorporation, nor particular host cell responses common to treatment with all OMVs. Given the diversity of species studied, their differences in envelope architecture and composition, the diversity of environmentally regulated bacterial processes, and the variety of interactions between bacteria and their abiotic and biotic environments, this is hardly surprising. Nevertheless, the ability of bacteria to control exported material in the context of a packaged insoluble particle, a vesicle, is emerging as a significant contribution to bacterial viability, biofilm communities, and bacterial‐host interactions. In this review, we focus on detailing important, recent findings regarding the content and functional differences in bacterially secreted vesicles that are influenced by growth conditions.